Why does he do that? : inside the minds of angry and controlling men - Bancroft, Lundy (New York, NY : Berkley Books, 2002)
In this book, the author, a domestic violence expert uses his perspective as a therapist for abusive and controlling men to help women, their children, and other family members who have been touched by abuse understand why abusers behave the way they do and what can be done about it. He teaches women how to survive and improve an abusive relationship; how to determine how dangerous an abuser is and when it is impossible to rectify a situation; and how to get out of a relationship safely. He identifies nine types of abusive men, addressing different styles, from the physical batterer to the strictly verbal abuser. He dispels the pervasive societal myths surrounding abuse, exposing common excuses used by abusers, such as having experienced an abusive childhood or substance addiction. He answers commonly asked questions, such as what warning signs of abuse to look for early in a relationship; what is and is not abusive behavior; how to know if a woman and her children are in danger; and how to tell when a man is really changing.
Nature of Abusive Thinking. Mystery ; Mythology ; Abusive mentality ; Types of abusive men -- Abusive Man in Relationships. How abuse begins ; Abusive man in everyday life ; Abusive men and sex ; Abusive men and addiction ; Abusive man and breaking up -- Abusive Man in the World. Abusive men as parents ; Abusive men and their allies ; Abusive man and the legal system -- Changing the Abusive Man. Making of an abusive man ; Process of change ; Creating an abuse-free world.
Includes bibliographical references (p. 391-400) and index.
Keywords: Abusive men -- United States -- Psychology; Wife abuse -- United States; Family violence -- United States; Victims of family violence -- United States